Assessing thermal changes in the equine thoracolumbar region following different capacitive-resistive electrical transfer protocols - Calle-González, Natalie; Rivero, Jose-Luis L.; Olivares, Joaquín; Miró, Francisco; Argüelles, David; Requena, Francisco; Munoz, Ana (Frontiers in Veterinary Science, 2025)
IntroductionCapacitive-resistive electrical transfer (CRET) is an endogenous non-invasive technique, used as deep diathermy. We pursue to analyze the temperature changes by applying different CRET protocols in the thoracolumbar spine of horses, between thoracic vertebrae 15 and lumbar 2.MethodsTen clinically sound horses without thoracolumbar pain underwent various CRET protocols applied to a standardized thoracolumbar region (T15–L2). The protocols included sham (device off), low intensity (LIP, 5%), medium intensity (MIP, 30%), and high intensity (HIP, 40%). The HIP protocol was further divided into two-subprotocols based on the application of a subsequent low-intensity capacitive therapy: HIP+CAP (with capacitive therapy) and HIP-wCAP (without capacitive therapy). Skin minimum (Tmin), maximum (Tmax), and mean (Tmed) temperatures were assessed by thermography in degrees Celsius (°C) at assigned measurement times during application, and for 30 min post-therapy application.ResultsNo significant differences in Tmed and Tmax were found between sham and LIP protocols in any of the measurement times. During application, there were no significant differences between MIP and HIP protocols, but during the first 15 min after application, Tmed and Tmax were significantly higher in the HIP+CAP protocol (median and [interquartile ranges], 29.17°C [28.20–31.5°C]; 31.70°C [29.50–33.10°C]) compared to MIP (25.36°C [23.41–26.98°C]; p = 0.002; 27.58°C [26.15–28.10°C]; p = 0.001) and to HIP-wCAP (25.48°C [23.12–26.21°C]; p = 0.001; 28.22°C [27.10–29.21°C]; p = 0.004). At 30 min after CRET, Tmed and Tmax remained significantly higher in HIP+CAP (26.68°C [24.75–28.19°C]; 29.23°C [28.18–31.21°C]) compared to sham (23.16°C [22.11–25.23°C], p = 0.022; 25.15°C [23.12–27.10°C]; p = 0.001), and LIP (24.25°C [22.13–25.34°C], p = 0.023; 26.22°C [24.23–27.34°C]; p = 0.034).Main limitationsSkin temperature was measured, rather than using invasive techniques involving the insertion of thermal probes into muscles. Skin thickness and hair density may have affected temperature measurements.ConclusionsLow-intensity CRET induced similar temperatures compared to sham. Moderate and high-intensity protocols produced similar temperature increases; despite high-intensity sessions were limited to 10 min due to horse tolerance. Shorter high-intensity treatments may be easier to apply and adding a short time of low-intensity capacity therapy after high-intensity protocols, may help maintain elevated temperatures for longer periods of time, without significantly increasing the duration of therapy.